Impact of genes highly correlated with MMSET myeloma on survival of Non-MMSET myeloma patients - Wu, S. Peter (Clin Cancer Res, 2016)
PURPOSE: The poor prognosis of multiple myeloma with t(4;14) is driven by the fusion of genes encoding MMSET and immunoglobulin heavy chain. Specific genes affected by MMSET and their clinical implications in Non-MMSET myeloma remain undetermined. EXPERIMENTAL DESIGN: We obtained gene-expression profiles of 1,032 newly diagnosed myeloma patients enrolled in Total Therapy 2, Total Therapy 3, Myeloma IX, and HOVON65-GMMGHD4 trials, and 156 patients from Multiple Myeloma Resource Collection. Probes most correlated with MMSET myeloma were selected based on a multivariable linear regression and Bonferroni correction, and refined based on the strength of association with survival in Non-MMSET patients. RESULTS: Ten MMSET-like probes were associated with poor survival in Non-MMSET myeloma. Non-MMSET myeloma patients in the highest quartile of the 10-gene signature (MMSET-like myeloma) had 5-year overall survival similar to that of MMSET myeloma (highest quartile vs. lowest quartile hazard ratio [HR]=2.0, 95% confidence interval [CI] 1.5-2.8 in MMSET-like myeloma; HR=2.3, 95% CI: 1.6-3.3 in MMSET myeloma). Analyses of MMSET-like gene signature suggested the involvement of p53 and MYC pathways. CONCLUSION: MMSET-like gene signature captures a subset of high-risk myeloma patients under-represented by conventional risk stratification platforms, and defines a distinct biological subtype.